2002
DOI: 10.1038/nsb791
|View full text |Cite
|
Sign up to set email alerts
|

Structural properties of an amyloid precursor of β2-microglobulin

Abstract: The population of one or more partially folded states has been proposed as a critical initial step in amyloid formation for several proteins. Here we use equilibrium denaturation measured by (1)H-(15)N NMR to determine the conformational properties of an amyloidogenic intermediate of human beta(2)-microglobulin (beta(2)m) formed at low pH. The data show that this amyloid precursor is a noncooperatively stabilized ensemble that retains stable structure in five of the seven beta-strands that comprise the native … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
166
3

Year Published

2005
2005
2013
2013

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 191 publications
(188 citation statements)
references
References 30 publications
19
166
3
Order By: Relevance
“…Assignment of Urea-denatured State-To determine the structural characteristics of ␤-PrP on a per residue basis, it is necessary to recover the line-broadened signals, a task that is often readily achieved through the addition of a chemical denaturant (50,60). Previous experiments demonstrated that ␤-PrP is prone to aggregation at high ionic strength and therefore urea was used here as an alternative to guanidine hydrochloride, to minimize any aggregation (58).…”
Section: Resultsmentioning
confidence: 99%
“…Assignment of Urea-denatured State-To determine the structural characteristics of ␤-PrP on a per residue basis, it is necessary to recover the line-broadened signals, a task that is often readily achieved through the addition of a chemical denaturant (50,60). Previous experiments demonstrated that ␤-PrP is prone to aggregation at high ionic strength and therefore urea was used here as an alternative to guanidine hydrochloride, to minimize any aggregation (58).…”
Section: Resultsmentioning
confidence: 99%
“…10 In contrast, only about 40-60 resolved peaks on top of a broad hump of unresolved signal intensity (visible at lower contour levels) could be observed at pH 3.6 ( Figure 1a). 11 To obtain sequence-specific information about the pH 3.6 intermediate, we tested direct 13 C detection. [12][13][14] Direct carbon detection was previously successfully used for the study of unfolded proteins and to alleviate problems of exchange.…”
mentioning
confidence: 99%
“…This is consistent with the findings from other previous reports -an acetate buffer solution at pH 5.5 with trifluoroethanol was used to induce soluble oligomers of SH3 domain from bovine phosphatidyl-inositol-3'-kinase and the amino-terminal domain of the Escherichia coli HypF protein 21 . Human β 2 -microglobulin and transthyretin form amyloid fibrils efficiently under acidic conditions in vitro 22,24,25 . For functional amyloidogenic protein Pme17, a critical pH regime between 5 +/-0.5 is required for fibril formation in a specific melanosome compartment 26 .…”
Section: Discussionmentioning
confidence: 99%
“…This is dictated by the high protein concentration necessary to permit the effective aggregation of partially misfolded proteins in order to form soluble protein oligomers. Previously, protein-only amyloid has been generated by treating native proteins with high temperature, hydrophobic solvent, denaturing agents, or extreme pH exposure [19][20][21][22] . However, soluble protein oligomers, if detectable at all, are only formed temporarily in solution with very limited abundance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation